ISLAMIC FINANCING MECHANISM FOR SMALL MEDIUM ENTERPRISES IN AGRICULTURE SECTOR: A PROPOSED MODEL - Thuba Jazil (STES Islamic Village, 2019)
This paper aims to discuss the construction of proposed model on the Islamic financing mechanism of Islamic banking system for the agriculture and small medium enterprises sector. A qualitative approach used in this study employing the Participatory Rural Approach and Focus Group Discussion using Triangle Microfinance Concept. The result shows that the synergy of the various sectors ranging from the central government through the Institute of relevant Ministries e.i Ministry of Finance Ministry of Agriculture, Local Government, Non-Profit (Zakat) Organization (BAZNAS/LAZ), Universities, Non-Government Organisations, Supporting Institutions i.e. Islamic agriculture Insurance, Islamic Financing Deposit Insurance, and Rating Agency need to be synergized. Additionally, the distrust of Islamic banking industry is found to allocate a financing to farmers and SMEs actors. Farmers and SMEs actors should be prepared through the empowerment in terms of skills, moral and financial literacy. Establishment of Agriculture Purpose Vehicle is urgent to support the flow of Islamic Financing as to solve the problem of off-farm agriculture, collateral, and positive cooperative relationship.This paper contributes to the bridge the gap between the regulator, Islamic bank’s trust to farmers and SMEs development.